Polyvinyl alcohol film with chlorine dioxide microcapsules can be used for blueberry preservation by slow-release of chlorine dioxide gas - Su, Hongxia; Chen, Zhanpeng; Zhao, Yuan; An, Jiejie; Huang, Haohe; Liu, Ren; Huang, Chongxing (Frontiers in Nutrition, 2023)
Introduction Chlorine dioxide (ClO2) is a safe and efficient bactericide with unique advantages in reducing foodborne illnesses, inhibiting microbial growth, and maintaining the nutritional quality of food. However, gaseous ClO2 is sensitive to heat, vibration, and light, which limits its application. Methods In this study, a ClO2 precursor-stabilized ClO2 aqueous solution was encapsulated by the double emulsion method, and a high-performance ClO2 self-releasing polyvinyl alcohol (PVA) film was prepared to investigate its performance and effect on blueberry quality during storage. Results The self-releasing films had the best overall performance when the microcapsule content was 10% as the film's mechanical properties, thermal stability, and film barrier properties were significantly improved. The inhibition rates of Listeria monocytogenes and Escherichia coli were 93.69% and 95.55%, respectively, and the mycelial growth of Staphylococcus griseus was successfully inhibited. The resulting ClO2 self-releasing films were used for blueberry preservation, and an experimental study found that the ClO2 self-releasing antimicrobial film group delayed the quality decline of blueberries. During the 14-day storage period, no mold contamination was observed in the ClO2 self-releasing film group, and blueberries in the antibacterial film group had higher anthocyanin accumulation during the storage period. Discussion Research analysis showed that films containing ClO2 microcapsules are promising materials for future fruit and vegetable packaging.